Entrepreneurial interest in startup business based on entrepreneurial literacy and digital literacy - Rike Setiawati; Zulfina Adriani; Besse Wediawati (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
It is the first empirical research that initiates a model for a growing interest in entrepreneurship among the younger generation based on the two most important literacy in the industrial era 4.0, namely digital literacy and entrepreneurial literacy. Specifically, the purpose of this research is to fill the research gap of the lack of research that examines the interest in entrepreneurship in startups based on digital literacy and entrepreneurial literacy as well as solving problems for the low interest in entrepreneurship in startup businesses among the younger generation. The sample of this research was 406 students of the Faculty of Economics and Business, Universitas Jambi. It was collecting data using a questionnaire. The data analysis technique used Partial least square. The study results showed high entrepreneurial and digital literacy levels and student interest in entrepreneurship. Entrepreneurial and digital literacy has a positive and significant effect on the entrepreneurial interest of students. To foster entrepreneurial interest in startup businesses, it is necessary to provide entrepreneurial literacy to the younger generation, both formally and informally. It is also necessary to increase digital literacy with an education relevant to startup businesses among the younger generation.